A PLA composite material for 3D printer consumables and preparation method thereof
By adding starch-modified lanthanum doped composite oxide particles to PLA materials and adopting high-temperature treatment and ball-mill modification processes, the limitations of PLA materials in terms of mechanical properties, thermal stability and printing properties are solved, and its heat resistance, UV and wear resistance are significantly improved, making it more suitable for 3D printer consumables.
Patent Information
- Application Number
- CN202411385038.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Existing PLA materials have limitations in mechanical properties, thermal stability and printing properties, and cannot meet the needs of certain specific application fields. They are not heat-resistant, easy to become soft, sensitive to acids, alkalis, alcohols and water, and are not resistant to UV light.
PLA composite materials are used, which contain 85% to 95% PLA, 4% to 12% modified filler, 0.5% to 2.0% emulsifier and 0.5% to 1.5% coupling agent. The modified filler is starch-modified lanthanum doped composite oxide particles, and the heat resistance, UV resistance and wear resistance of the material are improved through high-temperature treatment and ball-mill modification processes.
The heat resistance, UV resistance and wear resistance of PLA materials are significantly improved, making them more suitable for 3D printer consumables, with high environmental adaptability and service life.
Smart Images

Figure BDA0005070803930000211 
Figure BDA0005070803930000221
Abstract
Description
Technical Field
[0001] The present invention relates to the field of 3D printing materials, and in particular to a PLA composite material used as consumables for 3D printers and a preparation method thereof. Background Art
[0002] With the rapid development of 3D printing technology, the demand for 3D printer consumables is increasing. Currently, the most common 3D printing consumables on the market are mainly PLA (PLA) materials, because of their good biodegradability, non-toxicity and easy processing. However, the mechanical properties, thermal stability and printing performance of pure PLA materials still have certain limitations and cannot meet the needs of certain specific application fields.
[0003] CN104327470B discloses a modified PLA material for a 3D printer, comprising the following components in parts by weight: 30-88 parts of PLA; 2-25 parts of toughening agent; 0.5-18 parts of nano oxide; 5-30 parts of lignin; 4-35 parts of polyacrylate; 1-12 parts of crosslinking agent; 2-20 parts of filler; and 1-10 parts of coupling agent. The lignin in the present invention can form a network structure and be dispersed inside the PLA structure, thereby improving the strength of the PLA through the network structure; the coupling agent is used to improve the dispersibility of the filler in the PLA, thereby further improving the effect of the filler in enhancing the impact resistance of the material; the nano oxide is a fine particle, and the nano particles have strong rigidity. When the cracks in the molecular structure are extended, they encounter the nano particles and deflect, absorbing energy to achieve the purpose of toughening.
[0004] CN110016214B discloses a PLA blended modified material for 3D printing and a preparation method thereof, first P3 / 4HB and PLA are respectively put into a pulverizer for pulverization, pulverized to P3 / 4HB as particles with a diameter of 6mm, PLA as particles with a diameter of 5mm, and then placed in a vacuum drying oven for drying; then fillers, lubricants and antioxidants are treated accordingly, and placed dry; then PLA-alt-P3 / 4HB is synthesized; finally, P3 / 4HB, PLA and PLA-alt-P3 / 4HB of different proportions are weighed, and mixed in a high-speed mixer, and mixed uniformly by a twin-screw extruder, melt blending and extrusion, to obtain a blended material. The present invention is blended with PLA using P3 / 4HB of different components, and PLA-P3 / 4HB polyurethane is synthesized by polymerization reaction, and PLA-P3 / 4HB polyurethane is added to increase the compatibility of PLA and P3 / 4HB materials, and fillers such as talcum powder and wollastonite are added to enhance the blended material.
[0005] CN106243655B discloses a high-strength PLA material for 3D printing, including the following components by mass: 100 parts of left-handed PLA resin, 1-20 parts of inorganic filler, 0.01-5 parts of polycarboxylic acid metal salt, 0.1-5 parts of amide compound, 0.1-5 parts of plasticizer, 0.1-1 parts of antioxidant and 0.1-2 parts of anti-hydrolysis agent; the anti-hydrolysis agent is at least one of polycarbodiimide compound, monocarbodiimide compound and acrylic copolymer with active group epoxy group; the inorganic filler is a mixture of one or at least two of nano-silicon dioxide, talcum powder, calcium sulfate whisker and mica, and the diameter of the inorganic filler is 0.05-10μm. The mechanical properties of the present invention are also improved, the tensile strength of the material reaches more than 63MPa, and the brittleness of PLA itself is changed at the same time, and it can also withstand greater pressure and wear.
[0006] The above technologies have made many improvements in the strength of PLA used in 3D printer consumables, but PLA material is not heat-resistant and easily softens (may bend or twist, especially at about 60°C) or even melts. PLA is also sensitive to acids, alkalis, alcohols and water, especially under melting conditions, and is prone to degradation. At the same time, it is also not resistant to UV light and has the problem of insufficient durability in outdoor applications. Summary of the invention
[0007] In order to solve the above problems, the present invention proposes a PLA composite material for 3D printer consumables and a preparation method thereof, which has good heat resistance, high adaptability to the environment, abrasion resistance, and strong tolerance to UV light.
[0008] To achieve the above object, the technical solution of the present invention is:
[0009] A PLA composite material for 3D printer consumables comprises, by weight, 85% to 95% PLA, 4% to 12% modified filler, 0.5% to 2.0% emulsifier, and 0.5% to 1.5% coupling agent; the modified filler is starch-modified lanthanum-doped composite oxide particles, and the mass percentage of lanthanum in the starch-modified lanthanum-doped composite oxide particles is 0.01% to 0.7%.
[0010] The method for preparing starch-modified lanthanum-doped composite oxide particles comprises the following steps:
[0011] Step (a-1): Mixing bentonite and lanthanum oxide in a mass ratio of 100-200:1, and refining to obtain a mixture;
[0012] Step (a-2): adding 1 part of the mixture obtained in step (a-1) to 3-5 parts of acetic acid solution with a mass concentration of 30%-50%, standing for 10-30 minutes and then press-forming to obtain a blank;
[0013] Step (a-3): inserting an electrode into the blank obtained in step (a-2), applying electricity for 10-30 minutes, then adding 5-15 parts of water, stirring, gelatinizing for 10-30 minutes, then dehydrating, carbonizing, high-temperature treating, crushing and sieving to obtain composite particles;
[0014] Step (a-4): Add the composite particles obtained in step (a-3) and a starch solution with a concentration of 0.5%-2% in a ratio of 1:1-3 into a ball mill and ball mill for 0.5-3h, then unload and dry to obtain starch-modified lanthanum-doped composite oxide particles.
[0015] This solution improves the performance by adding fillers to PLA. This solution uses bentonite as the filler raw material, but conventional bentonite easily absorbs water and swells. If it is added directly, it will not only fail to play a strengthening role, but will also swell when it encounters water and shrink when it loses water, resulting in the formation of microcracks and reducing the strength of 3D printed parts. Therefore, it needs to be further processed before use.
[0016] This scheme first mixes and refines bentonite and lanthanum oxide to increase the specific surface area. Step (a-2) adds the mixture to the acetic acid solution and allows it to stand for 10-30 minutes. The standing process is for: 1. The bentonite in the mixture can absorb a portion of the acetic acid solution to expand the volume; 2. Give lanthanum oxide and acetic acid reaction time. In the acetic acid solution absorbed by the bentonite, a portion of the hydrogen ions will replace the original metal ions, so that the replacement capacity of the bentonite becomes larger, and the reaction of the hydrogen ions generated by the ionization of acetic acid and lanthanum oxide occurs at the contact surface between the bentonite particles and the lanthanum oxide particles, which is equivalent to the exchange of lanthanum ions with hydrogen ions in the bentonite, so that the lanthanum ions can quickly enter the interlayer of the bentonite. The acetic acid solution that is not absorbed reacts with the lanthanum oxide particles, and the efficiency of the generated lanthanum ions entering the bentonite is low. Pressure molding can discharge some of the acetic acid solution absorbed by the bentonite, and also discharge a portion of the light metal ions, so that the interlayer spacing of the bentonite becomes smaller. This process also reduces the spacing between the particles, which can hinder the movement of ions.
[0017] In step (a-3), the energization treatment causes the free ions in the blank to move in a directional manner, among which hydrogen ions are the fastest moving, followed by sodium ions with smaller atomic weight and electric charge, and the slowest are heavy ions such as lanthanum. Its main functions are: 1. The electrolysis reaction that occurs after the electrode is energized is mainly the electrolysis of water. After the cathode generates hydrogen, the residual hydroxide will first react with light metals with faster movement rates such as calcium and aluminum to form precipitates, and subsequent lanthanum ions have more opportunities to enter the bentonite interlayer; 2. Activate bentonite and increase ion exchange capacity. Then add water and stir, and the role of gelatinization treatment is: 1. Stirring, the distance between bentonite layers becomes larger during gelatinization treatment, and more lanthanum ions can enter the bentonite interlayer (pressurization molding reduces the distance in order to allow the light metal ions between bentonite layers to be discharged with the acetic acid solution; and gelatinization treatment is that part of the light metal has been converted into precipitation, and lanthanum ions can enter the bentonite interlayer more effectively); 2. Make the light metal precipitate evenly dispersed between bentonite particles. Carbonization treatment can precipitate and solidify free ions such as calcium and aluminum remaining after dehydration, preventing them from segregating with water evaporation during subsequent high-temperature treatment.
[0018] Under the action of dehydration and high temperature treatment in step (a-3), the original structure of bentonite is destroyed and loses its water absorption effect, that is, it no longer has the effect of swelling when exposed to water. During the high temperature treatment process, lanthanum ions and silicon, calcium and other ions in bentonite form composite oxides, which can show a good absorption effect on ultraviolet rays, thereby improving the anti-ultraviolet ability of the printed part. During the high temperature treatment process, the residual acetate gradually precipitates between the bentonite particles and layers as the temperature rises; when the temperature rises above 700°C, the acetate ions decompose in large quantities, generating micropores on the surface of the particles, and the residues can form active sites; further heating to above 850°C, solid phase reaction begins to be realized, especially through ion exchange, the dispersed lanthanum ions inserted between the layers form a composite oxide structure with elements such as calcium, silicon, and oxygen, so that the band structure changes, providing a guarantee for UV light tolerance.
[0019] The role of step (a-4) is to modify the surface of the composite particles. Since the composite particles have a low bonding strength with PLA, direct use may result in a large number of pores. By modifying the surface of the composite particles with starch, the bonding strength between the composite particles and PLA can be improved. Under the action of ball milling, the composite particles produce new interfaces and expose metal cations, so these new interfaces have high activity. In the starch solution, there are a large number of oxygen elements in the starch molecules. The high-valent metals such as lanthanum and aluminum in the composite particles will capture these elements, thereby improving the adhesion of starch molecules to the surface of the composite particles.
[0020] Preferably, the emulsifier has an HLB of 12 to 16; and the coupling agent is at least one of silanes and titanates.
[0021] Preferably, in step (a-1), the cation exchange capacity of the bentonite is 0.05-0.15 mmol / g; and the average particle size of the mixture is 0.5-1.0 μm.
[0022] In order to retain as many lanthanum ions as possible in the composite particles to form composite oxides with silicon, calcium and other ions in the bentonite, the cation exchange capacity of the bentonite is controlled to be above 50 mmol / g.
[0023] Preferably, in step (a-3), the gelatinization treatment is carried out under ultrasonic conditions of 20-100 kHz for 10-60 min.
[0024] Bentonite has a layered silicate structure at the microscopic level. Ultrasonic treatment can change the interlayer spacing of bentonite, making it easier for lanthanum ions in the solution to enter.
[0025] Preferably, in step (a-2), the pressure of the pressurized molding is 0.1-1 Mpa. The molding pressure should not be too high, as it will make it difficult for the light metal ions to move.
[0026] Preferably, in step (a-3), the current of the energization treatment is 0.01-0.1A.
[0027] Preferably, the carbonization treatment is performed under a carbon dioxide atmosphere for 10-20 minutes.
[0028] Preferably, in step (a-3), the dehydration process is filter press dehydration, and the moisture content after dehydration is 5%-10%; the average particle size of the composite particles is 3-10 μm.
[0029] During the dehydration process, the replaced sodium and calcium ions and the unreplaced lanthanum ions will be lost along with the water, and the number of unreplaced lanthanum ions is much larger than the lanthanum ions replaced into the bentonite; the composite particles also need to be ball-milled in step (a-4), and the ball-milling process is a surface modification process, and the water-soluble starch molecules will adhere to the surface of the new grain boundaries. The average particle size before ball-milling should not be too fine, as it will reduce the number of new grain boundaries, resulting in poor modification effect, and also increase the difficulty of screening, which is not conducive to subsequent unloading.
[0030] Preferably, in step (a-3), the high temperature treatment condition is 900-1000°C for 1-3h; the heating process of the high temperature treatment is: when the temperature is lower than 400°C, the heating rate is 10-20°C / min, and when the temperature is higher than 400°C, the heating rate is 3-5°C / min.
[0031] The temperature at which bentonite loses its water absorption is between 300-400°C. This process is to volatilize the water as quickly as possible, so that the distribution of precipitates between bentonite layers can be more uniform, making the performance after high-temperature treatment more stable. The decomposition temperature of acetate is above 700°C. In order to ensure the complete decomposition of the residual acetate, the insulation temperature should be above 750°C. At the same time, at temperatures above 800°C, the dispersed lanthanum ions enter the lattice of metal oxides such as calcium and aluminum through diffusion, or form a lanthanum-doped glass phase with silicon dioxide, etc., that is, the combination of these complex phases is the composite oxide described in this scheme, so it must be kept warm at above 800°C. However, if the temperature is too high (over 1000°C) or the insulation time is too long, the grains grow at high temperature, resulting in a larger size, which will reduce the absorption of ultraviolet rays and also affect the subsequent combination with PLA.
[0032] Preferably, in step (a-4), the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the balls is 1:3-7; the drying conditions are 60-80°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is less than 0.5%, and the average particle size is 0.8-1 μm.
[0033] Ball milling will increase the number of grain boundaries, especially for bentonite, which is a 2:1 layered silicate mineral composed of two layers of silicon-oxygen tetrahedral sheets and a layer of aluminum-oxygen octahedron sandwiched between them. After high-temperature treatment, although the basic crystal structure of bentonite has been destroyed, it will still maintain a layered arrangement, but the interaction force is weakened. This layered arrangement structure can be further separated during the ball milling process, so that the doped lanthanum element can be better exposed. The use of vacuum drying can make the starch molecules that are not captured by the composite particles coated with the composite particles during the drying process. At the same time, the vacuum process can also discharge the gas in the pore structure on the surface of the composite particles, making the starch molecules more firmly attached and reducing the air brought in during the subsequent blending process.
[0034] The present invention also discloses a method for preparing a PLA composite material for 3D printer consumables, comprising the following steps:
[0035] Step (a): preparing a modified filler;
[0036] Step (b): drying the PLA substrate;
[0037] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), an emulsifier, and a coupling agent are blended and granulated in proportion, and then the mixed particles are extruded by a screw, and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0038] Preferably, the drying treatment condition in step (b) is 80-90° C. for 1-10 h.
[0039] Preferably, the extrusion molding temperature in step (c) is 220-250°C.
[0040] The drying condition is generally 85°C for 8 hours, and the extrusion temperature is 220-250°C to ensure fluidity and allow air to be fully discharged. The blending process of step (c) will fully mix the modified filler, i.e. the starch-modified lanthanum-doped composite oxide particles, in the molten PLA.
[0041] Compared with the existing technology, the advantages of this solution are:
[0042] 1. The present invention proposes a PLA composite material for 3D printer consumables, which has good heat resistance, high adaptability to the environment, abrasion resistance, and strong tolerance to UV light.
[0043] 2. The preparation process of starch-modified lanthanum-doped composite oxide particles proposed in this scheme is simple and low-cost. The phase-free transformation between substances is fully considered during the preparation process. The prepared starch-modified lanthanum-doped composite oxide particles can be fully dispersed in the PLA substrate. At the same time, during the 3D printing process, the starch-modified lanthanum-doped composite oxide particles can be used as a nucleating agent. Under the action of the coupling agent and starch, the molten PLA molecular chain nucleates on the surface of the starch-modified lanthanum-doped composite oxide particles. After cooling and solidification, the starch-modified lanthanum-doped composite oxide particles can hinder the movement of the PLA molecular chain and improve the mechanical strength. At the same time, the lanthanum element exchanges with the cations in the bentonite, so that a complex lanthanum-doped oxide structure is obtained after high-temperature treatment, which makes the material's UV resistance stronger. DETAILED DESCRIPTION
[0044] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0045] Example 1
[0046] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0047] Step (a): preparing a modified filler, comprising the following steps:
[0048] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0049] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0050] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0051] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%.
[0052] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15% and the average particle size was 1 μm;
[0053] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 90%, 7.0%, 1.2%, and 1.3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0054] Example 2
[0055] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0056] Step (a): preparing a modified filler, comprising the following steps:
[0057] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0058] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0059] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0060] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm.
[0061] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0062] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 88%, 10.0%, 1.0% and 1.0%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0063] Example 3
[0064] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0065] Step (a): preparing a modified filler, comprising the following steps:
[0066] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0067] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0068] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0069] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 0.9 μm.
[0070] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0071] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 94%, 5.0%, 0.5% and 0.5%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0072] Example 4
[0073] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0074] Step (a): preparing a modified filler, comprising the following steps:
[0075] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0076] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0077] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0078] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 0.9 μm.
[0079] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0080] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 88%, 10.0%, 1.0% and 1.0%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0081] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0082] Step (a): preparing a modified filler, comprising the following steps:
[0083] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0084] Step (a-2): preparing a 10% lanthanum acetate solution;
[0085] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0086] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85°C and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 0.8μm.
[0087] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0088] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 85%, 12.0%, 2.0% and 1.0%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0089] Example 5
[0090] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0091] Step (a): preparing a modified filler, comprising the following steps:
[0092] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0093] Step (a-2): preparing a 10% lanthanum acetate solution;
[0094] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0095] Step (a-4): adding the composite particles obtained in step (a-3) and a 2% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying condition is 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm;
[0096] Step (b): The PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%.
[0097] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 90%, 7.0%, 1.2%, and 1.3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0098] Comparative Example 1
[0099] Bentonite that has only been subjected to high temperature treatment is selected as filler, and the addition ratio and production process are the same as those in Example 1.
[0100] Comparative Example 2
[0101] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0102] Step (a): preparing a modified filler, comprising the following steps:
[0103] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0104] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0105] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0106] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm;
[0107] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0108] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 96%, 4.0%, 0% and 0%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0109] Comparative Example 3
[0110] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0111] Step (a): preparing a modified filler, comprising the following steps:
[0112] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0113] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0114] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0115] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm;
[0116] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0117] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, and the weight ratios of the components are 98%, 1.0%, 0.5% and 0.5%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and after cooling, a PLA composite material for 3D printer consumables is obtained.
[0118] Comparative Example 4
[0119] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0120] Step (a): preparing a modified filler, comprising the following steps:
[0121] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0122] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0123] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0124] Step (a-4): adding the composite particles obtained in step (a-3) and a 1% starch solution in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm;
[0125] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0126] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 80%, 15%, 2%, and 3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0127] Comparative Example 5
[0128] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0129] Step (a): preparing a modified filler, comprising the following steps:
[0130] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0131] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0132] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 950°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.5 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0133] Step (a-4): adding the composite particles obtained in step (a-3) and a starch suspension with a solid content of 1% in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 1 μm;
[0134] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0135] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 90%, 7.0%, 1.2%, and 1.3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0136] Comparative Example 6
[0137] This comparative example is pure PLA.
[0138] Comparative Example 7
[0139] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0140] Step (a): preparing a modified filler, comprising the following steps:
[0141] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0142] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0143] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 1100°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 7.0 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0144] Step (a-4): adding the composite particles obtained in step (a-3) and a starch solution with a concentration of 1% in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 2 μm;
[0145] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0146] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 90%, 7.0%, 1.2%, and 1.3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0147] Comparative Example 8
[0148] A method for preparing a PLA composite material for 3D printer consumables comprises the following steps:
[0149] Step (a): preparing a modified filler, comprising the following steps:
[0150] Step (a-1): refining bentonite having a cation exchange capacity of 0.1 mmol / g to an average particle size of 0.7 μm to obtain refined bentonite;
[0151] Step (a-2): preparing a lanthanum acetate solution with a concentration of 20%;
[0152] Step (a-3): adding the refined bentonite obtained in step (a-1) to the lanthanum acetate solution obtained in step (a-2) at a mass ratio of 1:10, then ultrasonically treating for 30 minutes under 80kHz ultrasonic conditions to perform cation replacement, dehydrating to a water content of 8% after the replacement treatment, high-temperature treating at 800°C for 1 hour, crushing and sieving to obtain composite particles with an average particle size of 5.0 μm; the heating process of the high-temperature treatment is: when the temperature is lower than 400°C, the heating rate is 15°C / min, and when the temperature is higher than 400°C, the heating rate is 3°C / min.
[0153] Step (a-4): adding the composite particles obtained in step (a-3) and a starch solution with a concentration of 1% in a ratio of 1:2 into a ball mill and ball milling for 3 hours, then unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles; the starch solution is a water-soluble starch solution or a soluble starch solution; during the ball milling process, the weight ratio of the material balls is 1:5; the drying conditions are 85° C. and vacuum drying; the moisture content of the starch-modified lanthanum-doped composite oxide particles is 0.15%, and the average particle size is 2 μm;
[0154] Step (b): the PLA substrate was dried at 85° C. for 8 h, and the moisture content after drying was 0.15%;
[0155] Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), the emulsifier with an HLB of 15, and the titanate coupling agent are blended and granulated in proportion, with the weight ratios of the components being 90%, 7.0%, 1.2%, and 1.3%, respectively. The mixed particles are then extruded by a screw at a temperature of 220° C., and a PLA composite material for 3D printer consumables is obtained after cooling.
[0156] Performance testing:
[0157] Tensile properties: refer to ASTM D3039 / D3039M-17;
[0158] Wear resistance: Refer to GB / T3960-2016, carry out wear test on plastic materials under certain conditions, and evaluate its wear resistance by measuring the wear amount, wear amount = wear mass / initial mass × 100%;
[0159] Anti-ultraviolet performance: refer to ASTM D3039 / D3039M-17 and GB / T 21196.2 for sample preparation. The prepared samples were exposed to 50°C and 85% relative humidity, and irradiated with 320nm ultraviolet light for 30 days. The surface morphology was observed, and the tensile properties and wear resistance were tested.
[0160] The samples of the above performance test methods were prepared by 3D printing. The simple process of 3D printing is: modeling → preheating → loading → printing. The material in the loading process is the PLA composite material used for 3D printer consumables in this scheme, and the printing temperature is 230°C.
[0161] Lanthanum doping amount: obtained by fluorescence spectroscopy.
[0162] Table 1
[0163]
[0164]
[0165] It can be seen from the data in Table 1 that Examples 1-5 have obvious mechanical advantages, wear resistance advantages and anti-ultraviolet light advantages over Comparative Examples 1-7 in terms of performance. This is mainly due to the fact that during the preparation process, the starch-modified lanthanum-doped composite oxide particles themselves have general filler properties (improved wear resistance), and at the same time, due to the complex phase composition, the energy band structure of the grains of each phase is complex, showing a good absorption capacity for ultraviolet light and better adaptability to the environment. If the conventional filler is not strongly bonded to the base material, it will cause microcracks to form on the contact surface, but in this solution, the ball milling modification process takes into account the auxiliary role of coupling agents, etc., and solves the problem of filler affinity with the base material. Therefore, the filler in the present invention mainly provides resistance to the molecular movement of the base material, thereby hindering the generation and expansion of cracks and having a higher tolerance to temperature.
[0166] As can be seen from Comparative Example 6, the tensile strength of pure PLA can reach 61.6MPa, but its wear resistance is particularly poor, which is related to the molecular structure of its polymer. After ultraviolet treatment, both tensile strength and wear resistance show great degradation. In combination with Comparative Example 1, it can be seen that only bentonite treated at high temperature can be added as a filler to improve wear resistance, but the compatibility between this filler and the base material PLA is not good, and the contact surface between the filler and the base material PLA becomes a source of microcracks, so the mechanical properties are worse than those of Example 1; further combined with Comparative Example 5, it can be seen that although the filler of Comparative Example 5 is treated with lanthanum substitution to obtain a complex oxide structure, there is a certain improvement in anti-ultraviolet performance, but the process of preparing starch-modified lanthanum-doped composite oxide particles does not use water-soluble starch, and surface modification cannot be achieved, resulting in poor compatibility between the filler and PLA. In addition, Comparative Example 5 uses conventional starch, and general starch will absorb water, gelatinize, swell, etc. in water, so it is easy to introduce such properties after being added to plastics, resulting in reduced plastic performance, such as the performance results of Comparative Example 5. However, this scheme uses water-soluble starch as a ball milling modifier in the form of a low-concentration solution, which is completely different from the particle system. Its water absorption capacity is inherently worse than that of ordinary starch, and its distribution on the particle surface is extremely small, so this inferior property can be ignored.
[0167] Comparative Examples 2, 3, and 4 are differences in composition ratios. It can be seen that when the composition ratio exceeds the specified range of this scheme, there are always deficiencies in tensile properties, wear resistance, and UV resistance. The basic rule is that when there are too many modified fillers, the tensile properties decrease, and the wear resistance and UV resistance are better; otherwise, the tensile properties are better.
[0168] Comparative Example 7 shows the effect of the average particle size of starch-modified lanthanum-doped composite oxide particles. The average particle size has a great influence on the dispersibility and performance effect. In this scheme, the average particle size is controlled by high-temperature treatment and ball milling. The high-temperature treatment temperature is high, the insulation time is long, the high-temperature stage heating time is long, and the average particle size is high; the ball milling time is short, the ball-to-material ratio is small, and the average particle size is large. However, the average particle size is too small. In addition to the increased difficulty of ball milling and other refinement operations, powder agglomeration is also very common, resulting in uneven overall performance distribution, thereby reducing the service life of the material, as shown in Comparative Example 8. Since the decomposition temperature of the residual acetate is relatively high, high-temperature treatment at a temperature below 800°C is likely to still have undecomposed acetate, and the temperature does not meet the solid-phase reaction requirements of the composite oxide, resulting in reduced solid-phase reaction efficiency and finer grains, which ultimately affects performance.
[0169] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A PLA composite material for 3D printer consumables, characterized in that: The composition includes, by weight: PLA 85% to 95%, modified filler 4% to 12%, emulsifier 0.5% to 2.0%, coupling agent 0.5% to 1.5%; The modified filler is starch-modified lanthanum-doped composite oxide particles, and the mass percentage of lanthanum in the starch-modified lanthanum-doped composite oxide particles is 0.01%-0.7%; The method for preparing starch-modified lanthanum-doped composite oxide particles comprises the following steps: Step (a-1): Mixing bentonite and lanthanum oxide in a mass ratio of 100-200:1, and refining to obtain a mixture; Step (a-2): taking 1 part of the mixture obtained in step (a-1), adding it to 3-5 parts of acetic acid solution with a mass concentration of 30%-50%, standing for 10-30 minutes and then press-forming to obtain a blank; Step (a-3): inserting an electrode into the blank obtained in step (a-2), applying electricity for 10-30 minutes, then adding 5-15 parts of water, stirring, gelatinizing for 10-30 minutes, then dehydrating, carbonizing, high-temperature treating, crushing and sieving to obtain composite particles; Step (a-4): adding the composite particles obtained in step (a-3) and a starch solution with a concentration of 0.5%-2% in a ratio of 1:1-3 into a ball mill and ball milling for 0.5-3h, followed by unloading and drying to obtain starch-modified lanthanum-doped composite oxide particles.
2. The PLA composite material for 3D printer consumables according to claim 1, characterized in that: In step (a-1), the cation exchange capacity of the bentonite is 0.05-0.15 mmol / g; and the average particle size of the mixture is 0.5-1.0 μm.
3. The PLA composite material for 3D printer consumables according to claim 1, characterized in that: In step (a-2), the pressure of the pressurization molding is 0.1-1 MPa.
4. The PLA composite material for 3D printer consumables according to claim 1, characterized in that: In step (a-3), the current of the energization treatment is 0.01-0.1A.
5. The PLA composite material for 3D printer consumables according to claim 1, characterized in that: In step (a-3), the gelatinization treatment is carried out under ultrasonic conditions of 20-100 kHz for 10-60 minutes.
6. The PLA composite material for 3D printer consumables according to claim 2, characterized in that: In step (a-3), the dehydration process is filter press dehydration, and the moisture content after dehydration is 5%-10%; the average particle size of the composite particles is 3-10 μm; and the carbonization treatment condition is standing for 10-20 minutes in a carbon dioxide atmosphere.
7. The PLA composite material for 3D printer consumables according to claim 2, characterized in that: In step (a-3), the high temperature treatment condition is 900-1000°C for 1-3h; the heating process of the high temperature treatment is: when the temperature is lower than 400°C, the heating rate is 10-20°C / min, and when the temperature is higher than 400°C, the heating rate is 3-5°C / min.
8. The PLA composite material for 3D printer consumables according to claim 2, characterized in that: In step (a-4), during the ball milling process, the weight ratio of the balls is 1:3-7; the drying condition is 60-80° C., vacuum drying; and the moisture content of the starch-modified lanthanum-doped composite oxide particles is less than 0.5%.
9. A method for preparing a PLA composite material for 3D printer consumables as claimed in any one of claims 1 to 8, characterized in that: The steps include: Step (a): preparing a modified filler; Step (b): drying the PLA substrate; Step (c): The PLA substrate dried in step (b), the starch-modified lanthanum-doped composite oxide particles prepared in step (a), an emulsifier, and a coupling agent are blended and granulated in proportion, and then the mixed particles are extruded by a screw, and after cooling, a PLA composite material for 3D printer consumables is obtained.
10. The method for preparing a PLA composite material for 3D printer consumables according to claim 9, characterized in that: The drying treatment condition in step (b) is 80-90°C for 1-10 hours; and the extrusion molding temperature in step (c) is 220-250°C.
Citation Information
Patent Citations
A kind of modified PLA material for 3D printer
CN104327470B
Polylactic acid material for high strength 3D printing
CN106243655B
A PLA blend modified material for 3D printing and its preparation method
CN110016214B
Polylactic acid green nano-nucleating temperature resistance agent and preparation method of same
CN109401234A
Polylactic acid modified material for injection molding products and preparation method thereof
CN112063140A